2021
DOI: 10.1177/09726225211030829
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Between Road Safety and Economic Development: A Case Study of India

Abstract: This study examines the relationship between fatality risk (number of fatalities per 10,000 people), the level of motorization (number of vehicles per 10,000 people) and fatality rate (number of fatalities per 10,000 vehicles), and the real per capita GDP across Indian states and union territories. Two kinds of relationships—linear and log-linear—are examined. The study also aims to estimate the real per capita GDP after which the fatality risk shows a decreasing trend with further increase in per capita GDP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…According to the study, per capita GDP inflection points range between $7,7418.74 and $13,666.83. Sinha et al (2021) found that the risk of death tended to decrease with a further increase in GDP per capita in India. In the study, the GDP threshold value was calculated as ₹190,000-₹195,000.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the study, per capita GDP inflection points range between $7,7418.74 and $13,666.83. Sinha et al (2021) found that the risk of death tended to decrease with a further increase in GDP per capita in India. In the study, the GDP threshold value was calculated as ₹190,000-₹195,000.…”
Section: Literature Reviewmentioning
confidence: 99%